ANALISIS KEMAMPUAN BERPIKIR KREATIF DAN KEMANDIRIAN SISWA TERHADAP PENYELESAIAN MASALAH INTEGRAL - Sari, Suci Indah; Nafisah, Zawahir; Sihotang, Rohani D.; Pohan, Ainna Anggriani; Sari, Dwi Novita (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The ability to think creatively is important for students to have in the mathematics learning process. However, the fact is that students still have difficulty creating novelty when given a problem. This research analyzes students' creative thinking abilities regarding high, medium, and low learning independence in mathematics. This research is a quasi-experimental research with a pretest-pottest design. The subjects of this research were 20 grade 12 students at an Ira College Foundation High School in Medan. The research instruments used were mathematical thinking tests, scales, and attitudes about high, medium, and low learning independence. Data was collected using questionnaires, tests, and interviews. This research shows that subjects with high learning independence can fulfill the creative thinking indicators of fluency, micro, and novelty aspects so they are classified as very creative. Subjects with learning independence are meeting the creative thinking indicators, aspects of fluency, and desire to be creative. Meanwhile, subjects with low learning independence only meet the creative thinking indicators for the fluency aspect and are therefore classified as less creative. These findings complement research related to the importance of independent learning in explaining variations in students' creative thinking abilities